Human-Machine Collaboration and Emotional Intelligence in Industry 5.0 - Vajravelu, Ashok; Thanikachalam, Yamunarani; Abd Wahab, Mohd Helmy; Abdul Jamil, Muhammad Mahadi; Sivaranjani, S (IGI Global, 2024)
The fifth industrial revolution offers personalized job-seeking experiences, focusing on societal well-being beyond just job creation and growth. Industry 5.0 prioritizes sustainable production and worker safety, shifting from tech-centric approaches of Industry 4.0. This revolution emphasizes human-centric practices over dehumanization and technical advancements. It highlights the importance of soft skills like emotional intelligence in preparing the workforce for Industry 5.0. Understanding these skills can enhance staff readiness for the new era, emphasizing the role of emotional intelligence in workforce development for Industry 5.0's human-centered approach.